PEMBERDAYAAN FUNGSI KEPALA DESA SEBAGAI MEDIATOR PENYELESAI SENGKETA PASCA UNDANG-UNDANG NO. 6 TAHUN 2014 TENTANG DESA - , Anti Mayastuti, Moh. Jamin, Mulyanto (PARENTAL, 2015)
AbstractDetermination Undang-Undang No. 6 of 2014 Village brings a new paradigm to the direction of development in Indonesia. The village became the forefront of efforts to development movement that comes from community initiatives, in order to achieve welfare and prosperity, as well as equitable and sustainable. In the law mandates one village head functions as a mediator of dispute settlement at the village level. This function expands the role and functions of the head of the village, in addition to village administration. Despite the role of the village head as a judge villages or mediator, in the Law on the Village mandates that in order to strengthen the values of the community of the functions of the head of the village as a resolver of disputes based on local wisdom "turned on" again as the pattern of settlement of disputes by peaceful means, which is essentially the same as the consensus or consensus.Keyword : Undang-Undang No. 6 of 2014, the village chief, Mediator